(q-6)*6=12

Simple and best practice solution for (q-6)*6=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (q-6)*6=12 equation:


Simplifying
(q + -6) * 6 = 12

Reorder the terms:
(-6 + q) * 6 = 12

Reorder the terms for easier multiplication:
6(-6 + q) = 12
(-6 * 6 + q * 6) = 12
(-36 + 6q) = 12

Solving
-36 + 6q = 12

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + 6q = 12 + 36

Combine like terms: -36 + 36 = 0
0 + 6q = 12 + 36
6q = 12 + 36

Combine like terms: 12 + 36 = 48
6q = 48

Divide each side by '6'.
q = 8

Simplifying
q = 8

See similar equations:

| x^2+3xy-4y^2-12+x=0 | | tanx=31 | | 256x^2+81x^2=22 | | 7x+20=3x-4 | | 100y+500=1000-200y | | 2y^2-4y=o | | 1/5x-2=2 | | 256x^2+81x^2=25 | | -33=3(6+x) | | 4(5-x)=28 | | 256x^2+81x^2=5 | | 6x^5+9x^3-4x^2-6=0 | | X^2-10n-25=0 | | 114q=-1176-16q | | 16x^2+9x^2=5 | | x^2+21x-184=0 | | 28+9=34 | | -5(-4)(2)= | | 24q+18=24 | | 33=18q+27 | | 22-6q=19 | | 10x+3x+y+6z-5x+8y-2z= | | 8/9*1/7 | | 13=16q-1 | | 10-12y=2 | | x^3/x^4=0 | | x^3/x^4 | | x^5-x^2=x | | 7p-4=-8+9 | | 21-3/12-3 | | 1/8/1/3*2=x | | 8a+5b+7c-3a-2b-6c= |

Equations solver categories